Selected cutaneous adverse events in patients treated with ICI monotherapy and combination therapy: a retrospective pharmacovigilance study and meta-analysis - Lu, Wenchao; Zhang, Huiyun; Guo, Qixiang; Gou, Zhuoyue; Yao, Jiannan (Frontiers in Pharmacology, 2023)
Cutaneous adverse events are commonly reported immune-related adverse events (irAEs), some of them are serious or even life-threatening, and it is essential to study these specific cutaneous AEs to understand their characteristics and risk. We performed meta-analysis of published clinical trials for immune checkpoint inhibitors (ICIs) to evaluate the incidence of cutaneous adverse events, using data from PubMed, Embase, and the Cochrane database. A total of 232 trials with 45,472 patients were involved. Results showed that anti-PD-1 and targeted therapy combinations were associated with higher risk for most of the selected cutaneous adverse events. In addition, a retrospective pharmacovigilance study was conducted using the Food and Drug Administration (FDA) Adverse Events System database. Reporting odds ratio (ROR) and Bayesian information components (IC) were used to perform the disproportionality analysis. Cases were extracted from January 2011 to September 2020. We identified 381 (20.24%) maculopapular rash, 213 (11.32%) vitiligo, 215 (11.42%) Stevens-Johnson syndrome (SJS), and 165 (8.77%) toxic epidermal necrolysis (TEN) cases. For vitiligo, anti-PD-1/L1 combined anti-CTLA-4 therapy showed the strongest signal (ROR 55.89, 95%CI 42.34-73.78; IC025 4.73). Palmar-plantar erythrodysesthesia (PPE) was reported with the most significant association with combined anti-PD-1 / L1 and VEGF (R) -TKI inhibitors (ROR 18.67, 95%CI 14.77–23.60; IC025 3.67). For SJS/TEN, anti-PD-1 inhibitors showed the strongest signal (ROR 3.07, 95% CI 2.68–3.52, IC025 1.39). The median onset time of vitiligo and SJS/TEN was 83 days and 24 days respectively. Overall, in selected cutaneous AEs, each of them showed specific characteristics. It is necessary to realize their difference and take appropriate interventions in patients with different regimens.